Functional characterization of Plasmodium vivax hexose transporter 1 - Won, Jeong Yeon; Mazigo, Ernest; Cha, Seok Ho; Han, Jin-Hee (Frontiers in Cellular and Infection Microbiology, 2024)
Plasmodium vivax is the most widely distributed human malaria parasite. The eradication of vivax malaria remains challenging due to transmission of drug-resistant parasite and dormant liver form. Consequently, anti-malarial drugs with novel mechanisms of action are urgently demanded. Glucose uptake blocking strategy is suggested as a novel mode of action that leads to selective starvation in various species of malaria parasites. The role of hexose transporter 1 in Plasmodium species is glucose uptake, and its blocking strategies proved to successfully induce selective starvation. However, there is limited information on the glucose uptake properties via P. vivax hexose transporter 1 (PvHT1). Thus, we focused on the PvHT1 to precisely identify its properties of glucose uptake. The PvHT1 North Korean strain (PvHT1NK) expressed Xenopus laevis oocytes mediating the transport of [3H] deoxy-D-glucose (ddGlu) in an expression and incubation time-dependent manner without sodium dependency. Moreover, the PvHT1NK showed no exchange mode of glucose in efflux experiments and concentration-dependent results showed saturable kinetics following the Michaelis-Menten equation. Non-linear regression analysis revealed a Km value of 294.1 μM and a Vmax value of 1,060 pmol/oocyte/hr, and inhibition experiments showed a strong inhibitory effect by glucose, mannose, and ddGlu. Additionally, weak inhibition was observed with fructose and galactose. Comparison of amino acid sequence and tertiary structure between P. falciparum and P. vivax HT1 revealed a completely conserved residue in glucose binding pocket. This result supported that the glucose uptake properties are similar to P. falciparum, and PfHT1 inhibitor (compound 3361) works in P. vivax. These findings provide properties of glucose uptake via PvHT1NK for carbohydrate metabolism and support the approaches to vivax malaria drug development strategy targeting the PvHT1 for starving of the parasite.